Bithiazolidinylidene polymers: synthesis and electronic interactions with transition metal dichalcogenides. Issue 22 (17th May 2018) - Selhorst, Ryan; Wang, Peijian; Barnes, Michael; Emrick, Todd
Abstract : We describe the synthesis and characterization of polymers bearing sulfur-rich, electron-accepting bithiazolidinylidene (BT) groups, and probe their electronic impact on 2-D transition metal dichalcogenides (TMDCs). Abstract : We describe the synthesis of electron acceptors consisting of bithiazolidinylidene (BT) derivatives incorporated into solution processible polymers. Novel BT-containing polymers displayed p-doping behavior when in contact with the n-type transition metal dichalcogenide (TMDC) MoS2 . A work function (WF) increase of MoS2, resulting from contact with BT polymers, was measured by Kelvin probe force microscopy (KPFM), representing the first example of polymer p-doping of MoS2, which is beneficial for advancing the design of electronically tailored TMDCs.